Age Estimation Based on Children’s Voice: A Fuzzy-Based Decision Fusion Strategy - Seyed Mostafa Mirhassani; Alireza Zourmand; Hua-Nong Ting (The Scientific World Journal)
Automatic estimation of a speaker’s age is a challenging research topic in the area of speech analysis. In this paper, a novel approach to estimate a speaker’s age is presented. The method features a “divide and conquer” strategy wherein the speech data are divided into six groups based on the vowel classes. There are two reasons behind this strategy. First, reduction in the complicated distribution of the processing data improves the classifier’s learning performance. Second, different vowel classes contain complementary information for age estimation. Mel-frequency cepstral coefficients are computed for each group and single layer feed-forward neural networks based on self-adaptive extreme learning machine are applied to the features to make a primary decision. Subsequently, fuzzy data fusion is employed to provide an overall decision by aggregating the classifier’s outputs. The results are then compared with a number of state-of-the-art age estimation methods. Experiments conducted based on six age groups including children aged between 7 and 12 years revealed that fuzzy fusion of the classifier’s outputs resulted in considerable improvement of up to 53.33% in age estimation accuracy. Moreover, the fuzzy fusion of decisions aggregated the complementary information of a speaker’s age from various speech sources.